Analis Yuridis Penggunaan Ganja Untuk Keperluan Kesehatan Dalam Perspektif Kemanfaatan Guna Pemenuhan Hak Dasar Kesehatan Setiap Warga Negara - Purba, Indra Gunawan (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2024)
Marijuana has been a public issue in Indonesia for a long time. The 1970s are considered to be the year when marijuana was first known and consumed by many people. In narcotics law, marijuana is a class I narcotic which has a very high potential to cause dependence and is not used for therapy. However, several institutions have proposed that marijuana be legalized in Indonesia, apart from being considered to provide medical benefits, it also has economic potential. Marijuana is currently still classified as Category I Narcotics in the Narcotics Law, while the use of marijuana for health reasons in Law Number 36 of 2009 concerning Health is not specifically regulated. In Article 102 of the Health Law, the use of pharmaceutical preparations in the form of narcotics and psychotropic substances can only be done based on a doctor's or dentist's prescription and is prohibited from being misused. Marijuana cannot be used for medical purposes.. The perspective of the Indonesian Health Law sees the use of marijuana for medical purposes in Law Number 36 of 2009 concerning Health that demands for the legalization of marijuana cannot be separated from the health conditions of the Indonesian people. From several research results, marijuana can treat several diseases such as glaucoma, lung health, epilepsy, cancer cells, chronic pain, Alzheimer's, acne, diabetes, and HIV/AIDS. Therefore, the legal steps that can be taken to legalize the use of marijuana for medical purposes in Indonesia are by revising the Narcotics Law and removing marijuana from narcotics class I, due to the fact that the implementation of the Narcotics Law is no longer relevant to the current reality where that marijuana is really needed as an alternative treatment and marijuana itself has been proven to have extraordinary benefits in the medical world and with the fact that is happening now where the UN and the drug commission have removed marijuana and marijuana resin from schedule IV of the single convention on narcotics. Keywords: Legalization, Marijuana, Public health